A ocorrência do golfinho-nariz-de-garrafa (Tursiops truncatus) na Plataforma Continental Amazônica - ARAUJO, Cássia Viana (2020)
The bottlenose dolphin (Tursiops truncatus) is a small marine mammal of cosmopolitan habit. In Brazil it occurs all over the coast. Although this dolphin is the most studied among odontocetes, most dolphin studies come from the south of the country. In the northern region, the evidence of occurrence of the species is mostly associated with strandings records. Thanks to the active efforts of research groups in the region, the reality of species occurrence data has been updated, especially data about the ecology of the living individual. The objective of this study was to obtain information about the occurrence of individuals of T. truncatus species, as well as data about their group size, group composition and distribution along the Amazonian continental shelf (PCA) using visual monitoring. Twelve campaigns were carried out from February 2018 to February 2019 under the Costa Norte Project, where the aquatic biota monitoring activity was carried out along the Amazonian continental shelf (from Oiapoque - AP to São Luís - MA). As soon as the bottlenose dolphin (Tursiops truncatus) was observed on the surface, data such as number of individuals, group composition (between Adults and young), observed behavior (such as displacement, feeding, socialization and respiration) and georeferenced coordinates, were described in spreadsheets. During the twelve campaigns carried out, 225 individuals were sighted throughout the PCA. The group size ranged from 2 to 20 individuals, with an average of 3.33 and fashion equal to 2. The group composition showed that most sightings were adults (n = 201) and only 24 pups. The most observed behavior was displacement (61.3%), followed by socialization (30.2%) and food (4.44%). Its distribution along the PCA showed a possible hotspot pattern and a residence pattern, with individuals being sighted all along the vessel's course. These results suggest that PCA is a zone with the occurrence of T. truncatus throughout the year, in which individuals find in this region a suitable range for their activities. Even with the information presented here, a long-term study of the species off the north coast of Brazil is suggested. Therefore, in addition to knowledge about its distribution in the PCA that will serve for further conservation of the species, the data will contribute to the dissemination of data of the species in northern Brazil.